Assessment of a polyelectrolyte multilayer film coating loaded with BMP-2 on titanium and PEEK implants in the rabbit femoral condyle. (May 2016) - Guillot, R.; Pignot-Paintrand, I.; Lavaud, J.; Decambron, A.; Bourgeois, E.; Josserand, V.; Logeart-Avramoglou, D.; Viguier, E.; Picart, C.
Graphical abstract: Abstract: The aim of this study was to evaluate the osseointegration of titanium implants (Ti-6Al-4V, noted here TA6V) and poly(etheretherketone) PEEK implants induced by a BMP-2-delivering surface coating made of polyelectrolyte multilayer films. The in vitro bioactivity of the polyelectrolyte film-coated implants was assessed using the alkaline phosphatase assay. BMP-2-coated TA6V and PEEK implants with a total dose of 9.3 μg of BMP-2 were inserted into the femoral condyles of New Zealand white rabbits and compared to uncoated implants. Rabbits were sacrificed 4 and 8 weeks after implantation. Histomorphometric analyses on TA6V and PEEK implants and microcomputed tomography on PEEK implants revealed that the bone-to-implant contact and bone area around the implants were significantly lower for the BMP-2-coated implants than for the bare implants. This was confirmed by scanning electron microscopy imaging. This difference was more pronounced at 4 weeks in comparison to the 8-week time point. However, bone growth inside the hexagonal upper hollow cavity of the screws was higher in the case of the BMP-2 coated implants. Overall, this study shows that a high dose of BMP-2 leads to localized and temporary bone impairment, and that the dose of BMP-2 delivered at the surface of an implant needs to be carefully optimized. Statement of Significance: The presentation of growth factors from material surfaces currently presents significant challenges in academia, clinics and industry. Applying osteoinductive factors to different types of implants, made of metals or polymers, may improve bone repair in difficult situations. Here, we show the effects of an osteoinductive coating made of polyelectrolyte multilayer films on two widely used materials, titanium TA6V alloys and PEEK implants, which were implanted in the rabbit femoral condyle. We show that a too high dose of BMP-2 delivered from the screw surface has a negative short-term effect on bone regeneration in close vicinity of the screw surface. In contrast, bone formation was increased at early times in the empty spaces around the screw. These results highlight the need for future dose-dependence studies on bone formation in response to osteoinductive coatings.